A comparison of perioperative outcomes of laparoscopic versus open nephroureterectomy for upper tract urothelial carcinoma: a propensity score matching analysis - Afferi, Luca; Abufaraj, Mohammad; Soria, Francesco; D'Andrea, David; Xylinas, Evanguelos; Seisen, Thomas; Roupret, Morgan; Lonati, Chiara; DE LA Taille, Alexandre; Peyronnet, Benoit; Laukhtina, Ekaterina; Pradere, Benjamin; et al. (Minerva urology and nephrology, 2022)
BACKGROUND: Radical nephroureterectomy (RNU) with the concomitant excision of the distal ureter and bladder cuff is the current standard of care for the treatment of muscle invasive and/or high-risk upper tract urothelial carcinoma (UTUC). In small uncontrolled studies, laparoscopic RNU has been suggested to be associated with better perioperative outcomes compared to open RNU. The aim of our study was to compare the perioperative oncological and functional outcomes of open RNU versus laparoscopic RNU after adjusting for preoperative baseline patient-related characteristics. METHODS: We evaluated a multi-institutional retrospective database composed by 1512 patients diagnosed with UTUC and treated with open or laparoscopic RNU between 1990 and 2016. Perioperative outcomes included operative time, blood loss, and length of hospital stay, as well as postoperative complications, readmission, reoperation, and mortality rates at 30 and 90 days from surgery. A 1:1 propensity score matching estimated using logistic regression with the teffects psmatch function of STATA 13® (caliper 0.2, no replacement; StataCorp LLC; College Station, TX, USA) was performed using preoperative parameters such as: age, gender, Body Mass Index (BMI), and American Society of Anesthesiologists (ASA) Score. RESULTS: Overall, 1007 (66.6%) patients were treated with open and 505 (33.4%) with laparoscopic RNU. Open RNU resulted into shorter median operative time (180 vs. 230 min, P<0.001) and longer median hospital stay (10 vs. 7 days, P<0.001) in comparison to laparoscopic RNU. No statistically significant difference was identified for the other variables of interest (all P>0.05). At multivariable linear regression after propensity score matching adjusted for lymph node dissection and year of surgery, laparoscopic RNU resulted in longer operative time (coefficient 43.6, 95% CI 27.9-59.3, P<0.001) and shorter hospital stay (coefficient -1.27, 95% CI -2.1 to -0.3, P=0.01) compared to open RNU, but the risk of other perioperative complications remained similar between the two treatments. CONCLUSIONS: Laparoscopic RNU is associated with shorter hospital stay, but longer operative time in comparison to open RNU. Otherwise, there were no differences in other perioperative outcomes between these surgical modalities even after propensity score matching. The choice to offer laparoscopic or open RNU in the treatment of UTUC should not be based on concerns of different safety outcomes.
Keywords: karcinom z přechodných buněk; laparoskopie; Nephroureterectomy; lidé; tendenční skóre; nefroureterektomie; retrospektivní studie; Laparoscopy; Urinary Bladder Neoplasms; Carcinoma, Transitional Cell; nádory močovodu; nádory močového měchýře; Retrospective Studies; Ureteral Neoplasms; Propensity Score; Humans